(untitled) (Gestión y Gerencia, 2025)
The objective of this study was to systematically analyze, through a review of contemporary literature, how institutional theories explain the balance in the external pressures of organizations competing for conformity with internal demands for efficiency and innovation. Institutional theories have provided a solid framework for understanding how organizations are influenced by their environment, particularly by social norms, cultural expectations, and regulatory pressures. For this review, a bibliographic search was conducted using electronic database managers: Web of Science, Scopus, JSTOR, and Google Scholar, which has determined nine (9) articles with temporal relevance between 2020 and 2024. Considering the search criteria, the following keywords were used: (I) institutional theory, (II) organizational legitimacy, and (III) isomorphism. As a result, this article summarizes that organizations manage institutional pressures by balancing the need for conformity, internal efficiency, and innovation based on institutional theory, delineating the mechanisms through which institutional pressures influence organizational behavior, including coercive, mimetic, and normative forces. There are strategies such as decoupling, selective coupling, and institutional entrepreneurship, which organizations use to balance external demands with internal priorities. The review concludes that a holistic approach, which combines these perspectives, is essential to understand how organizations achieve recognition and ensure their effectiveness amid changing institutional complexities.